2019
DOI: 10.1002/fsn3.971
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the lipid of red carp (Cyprinus carpio) during frozen storage

Abstract: The aim of this study was to determine the oxidative stability of oil extracted from red carp fish frozen up to 9 months at −18°C. To assess oil stability of red carp fish, the analytical indexes and Fourier transform infrared (FTIR) spectroscopy were used. These methodologies used provided similar conclusions. Before frozen storage, the composition of fatty acids showed that red carp oil is a good source of polyunsaturated fatty acids (PUFAs) such as linoleic acid (C18:2ω‐6: 5.29% of total fatty acid), linole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…The FTIR spectra of the bigels showed that there was a sharp peak at 1740 cm −1 . This peak is associated with the -C=O stretching vibrations of the esters that are present in lipids and fatty acids [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of the bigels showed that there was a sharp peak at 1740 cm −1 . This peak is associated with the -C=O stretching vibrations of the esters that are present in lipids and fatty acids [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can lead to increased FFA and products of oxidation (e.g. Christie, 1984;Gullian-Klanian et al, 2017;Tenyang et al, 2019). Lower freezing temperatures and short-term storage are generally associated with lower lipid degradation (e.g.…”
Section: Storagementioning
confidence: 99%
“…In these cases, around 4% of the processed fish decomposes during transport and storage 10 . The biochemical processes involved in the deterioration of fish depend mainly on temperature; freezing and frozen storage between −18 °C and the reference temperature of cryopreservation of −80 °C were therefore tested to ensure the fish's freshness, safety, and quality 11‐14 . A temperature of −35 °C is recommended for the long‐term storage of fish by Tolstorebrov et al 14 .…”
Section: Introductionmentioning
confidence: 99%
“…10 The biochemical processes involved in the deterioration of fish depend mainly on temperature; freezing and frozen storage between −18 °C and the reference temperature of cryopreservation of −80 °C were therefore tested to ensure the fish's freshness, safety, and quality. [11][12][13][14] A temperature of −35 °C is recommended for the long-term storage of fish by Tolstorebrov et al 14 Changes in texture caused by protein denaturation and membrane rupture with increased oxidation, however, are still observed in some fish when stored for long periods at this temperature. 12,15 It is known that frozen products in a rubbery state exhibit mobility and recrystallization of unfrozen water causing these phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation